Tren Publikasi Tentang Model Kepemimpinan dalam Pelayanan Publik: Suatu Analisis Bibliometrik - Condro Rahino Mustikaning Pawestri; Imam Yuadi (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2023)
Research related to leadership models that focus on public service is currently experiencing an increase. This is based on the urgency of leadership in public service. With the phenomenon of the development of research on leadership models in public services, the question arises of how to apply the right leadership model for public services. On the basis of this problem formulation, this study aims to describe a leadership model in public services in the 2015-2020 period using bibliometric analysis which in the process uses the VOSViewer and Biblioshiny applications. The research results show that there are 54 keywords related to the topics discussed. Of the 54 keys found, 1,259 relationships were created between the subject and the keywords. Of the 1,259 linkages, there are 4,367 total link strengths. Based on the analysis of one of the most widely cited studies, it was found that the leadership model influences employees' innovative behavior by increasing the emotional approach. A leader can also influence his employees' behavior with the leadership model he applies. Therefore, selecting the right leadership model is necessary to create quality public services.